2019
DOI: 10.1007/s12182-019-0325-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-salinity-based enhanced oil recovery literature review and associated screening criteria

Abstract: A thorough literature review is conducted that pertains to low-salinity-based enhanced oil recovery (EOR). This is meant to be a comprehensive review of all the refereed published papers, conference papers, master's theses and other reports in this area. The review is specifically focused on establishing various relations/characteristics or "screening criteria" such as: (1) classification/grouping of clays that have shown or are amenable to low-salinity benefits; (2) clay types vs. range of residual oil satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Zhang et al also observed improved oil recovery (e.g., up to 13% original oil in place) from their laboratory studies at lower salinity, i.e., 1500 ppm of injection brine. The mechanism of the LSWI was not very well understood, but wettability alteration and IFT reduction were considered as key factors for improved oil recovery by the majority of the researchers. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al also observed improved oil recovery (e.g., up to 13% original oil in place) from their laboratory studies at lower salinity, i.e., 1500 ppm of injection brine. The mechanism of the LSWI was not very well understood, but wettability alteration and IFT reduction were considered as key factors for improved oil recovery by the majority of the researchers. ,, …”
Section: Introductionmentioning
confidence: 99%
“…While the mechanisms of LSWF to increase oil recovery have not been verified completely yet, the laboratory core floods and field tests have shown that rock/fluid interactions as well as the solution and surface chemistry play important roles [13][14][15][16][17]. It is widely agreed that the EOR by LSWF is related to wettability alteration toward more water wet conditions [18,19], which creates positive capillary forces and increases the microscopic sweep efficiency in heterogeneous pore systems [19].…”
mentioning
confidence: 99%
“…In explaining the production mechanisms during low-salinity water-flooding (LSWF), Chavan et al 40 argued that multicomponent ion exchange (MIE) plays a key role. MIE first expands and opens up the outer diffuse layer, and then monovalent ions within the injecting phase replace the divalent ions of the adsorption layer.…”
Section: Resultsmentioning
confidence: 99%